Pengaruh Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Arisuadi Sejahtera Abadi (ASA) - Yulia Dharmayanti; Sugeng Suroso; Ery Teguh Prasetyo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the effect of work stress and work discipline on the performance employees of PT. Arisuadi Sejahtera Abadi (ASA). The type of research used in this research is quantitative research. Where the object is employees of PT. Arisuadi Sejahtera Abadi. The sampling technique uses a non-probability sampling method with a saturated sample technique (census), namely all members of the population are used as samples, a total of 53 employees PT. Arisuadi Sejahtera Abadi (ASA). The data analysis method uses multiple linear regression. The data was processed using IBM SPSS Statistics 26. The results of this study show that (1) work stress has a negative and significant effect on the performance employees of PT. Arisuadi Sejahtera Abadi (ASA), (2) work discipline has a positive and significant effect on the performance employees of PT. Arisuadi Sejahtera Abadi (ASA) and (3) work stress and work discipline simultaneously and significantly influence the performance employees of PT. Arisuadi Sejahtera Abadi (ASA).